2015
DOI: 10.1111/pace.12626
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphism during Ventricular Tachycardia: A Distinguishing Feature between Cardiac Sarcoidosis and Idiopathic VT

Abstract: Pleomorphism and CLV during VT may be distinguishing features between IVT and VTs of CS origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The major findings of our study were: As we have previously reported, 3 it is not uncommon to see CLV in VT of patients with CS.The stability criterion, if used as an SVT discriminator, can delay detection in the VT zone (or fast VT zones in Medtronic devices when programmed “via VT”).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The major findings of our study were: As we have previously reported, 3 it is not uncommon to see CLV in VT of patients with CS.The stability criterion, if used as an SVT discriminator, can delay detection in the VT zone (or fast VT zones in Medtronic devices when programmed “via VT”).…”
Section: Discussionsupporting
confidence: 50%
“…VT in CS can be due to re‐entry (from scar), but in the early stage is more often related to inflammation leading to VT resulting from automaticity and triggered activity 4,5 . VT thus can have CLV and pleomorphism, 3 especially during this inflammatory phase. In general, all ICDs discriminate VT from SVT based on the following three criteria 6,7 : Onset (sudden vs gradual–VT or SVT, vs sinus tachycardia, respectively);Stability (stable vs unstable–VT vs AF); andMorphology (matching to sinus template vs not matching–SVT vs VT)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Polymorphic VT and cycle length variation during VT might be more in favour of CS. 29 VT tends to occur in the fibrotic stage of CS and mainly results from reentry circuits through regions of scars. 26 Another suggested mechanism for VT is abnormal automaticity from granulomas.…”
Section: Casementioning
confidence: 99%
“…However, reentrant arrhythmias are more likely to be monomorphic, but this is not exclusive. Recently, Panda, et.al., compared VT morphologies between CS and idiopathic VT and found that pleomorphism during VT was more common in CS than in idiopathic VT [9]. The group from UCLA has proposed a new entity, arrhythmogenic inflammatory cardiomyopathy in patients with occult sarcoidosis [10].…”
Section: Commentarymentioning
confidence: 99%